Divergent drivers of tree community composition in lowland and highland forests of the northern tropical Andes, Colombia (2016)
ABSTRACT: Identifying the determinants of tree species composition among contrasting altitudinal tropical forest types will improve our understanding of the main factors and processes controlling tree species’ distributions and patterns of diversity. The study area is located in the northwest region of Colombia. We used Redundancy Analysis (RDA) and a semi-log distance-decay model to analyze the in uence of climate, soil fertility, and spatial processes, such as dispersal limitation, on community composition. There were 3 distinct forest types: one in the highlands and two in the lowlands. In the lowlands, both the RDA and the semi-log linear models identified calcium concentrations as the most important explanatory variable for species composition (R2adj = 0.24; p = 0.001 and RMantel = 0.68; p = 0.006, respectively). In the highlands, the RDA only identified longitude as being a significant explanatory variable (R2adj = 0.24; p = 0.001), primarily determined by the biogeographical location of forests on either the West or the Central Cordillera of the Andes. In these neotropical forests, the factors determining tree species composition between lowlands and highlands varied in both extent and nature. Overall, our findings do not support the idea of a higher habitat-plant specialization in highlands than in lowlands due to greater geomorphologic and edaphic variation. Since tropical Andean ecosystems, and in particular highland forests, have received less attention than their lowland counterparts, our findings help to expand the current knowledge of factors and processes determining community composition of tropical montane forests.